Photosynthetic activity of Quercus ilex at the extremes of a transect between Mediterranean and submediterranean vegetation (Trieste NE Italy) - Tretiach, M.; Bolognini, G.; Rondi, A. (FLORA, 1997)
Microclimatic data and CO2 gas exchange rates were measured in thecoastal area near Trieste (NE Italy) in two groups of plants rowing at the extremes of a floristic-vegetational gradient between an evergreen Mediterranean maquis on the coast and a winter deciduous submediterranean woodland on the Karst plateau, where Q. ilex persists only sporadically but is still a co-dominant tree. Field data were recorded from sunrise to sunset during the periods of highest productivity and of maximum physiological stress. i.e. high temperatures and water deficit in summer, and low temperatures and strong, dry winds in winter. Photosynthesis was measured with a portable Infrared Gas Analyzer. Microclimatic data showed that summer and winter stress were more intense on the Karst plateau. Assimilation of the coastal population was higher because a positive CO2 balance was maintained during both stress periods. During summer drought stress diurnal assimilation of the inland population was just in balance with nocturnal leaf respiration. In winter, on the contrary, photosynthetic activity ceased almost completely for almost a week, due to the lower temperature regime and to strong, dry winter winds that caused severe mechanical damages and, more generally, a drastic shortening of the leaf life span. The competition ability of Q. ilex in ecotonal areas is briefly discussed on the basis of these results. Winter stress seems to be the main factor limiting the distribution of Q. ilex northwards.
The following values have no corresponding Zotero field: pub-location: VILLENGANG 2, D-07745 JENA, GERMANY publisher: GUSTAV FISCHER VERLAG
Keywords: competition; CO2; drought stress; gradient; photos